Managerial factors in investment risk: Evidence from Polish mutual funds - Dariusz Filip (Financial Internet Quarterly, 2020)
The aim of this study is to examine whether investment risk is related to the managerial factors characterising portfolio managers. The study employs four risk measures and a set of individual manager characteristics, including socio-demographic variables determining a manager profile. The analysis is conducted based on data for 144 portfolio managers from 43 domestic equity funds operating in Poland in the period 2000-2015. The examinations are made possible by using static panel models. The obtained results indicate the existence of a relationship between managerial characteristics and risk measures, such as: standard deviation, beta coefficient, tracking error and bear-market percentile ranking. To our knowledge, it is the first paper to evaluate the investment risk of Polish mutual funds in relation to managerial characteristics.
Keywords: G23; J24; M12; 330; mutual funds; investment risk; managerial characteristics; human capital